Etnoentomologi dalam kalangan kaum Orang Asli dan Melayu di Semenanjung Malaysia - Ismail, Nurul Ashikin (2014)
Traditional Knowledge (TK) is an inherited practice of specific ethnic communities related to the unique way of life of the ethnic. These included the use of natural resources in their daily life and the practice of using insects is known as ethnoentomology. There is lack of documentation of ethnoenomology and no scientific evidence of the claim. Therefore, research should be done to preserve the erosion of traditional knowledge and highlight the potential of insects. The objective of this study was to document ethnoentomological knowledge by the Malays and Orang Asli in Peninsular Malaysia and then compared them to those in Sabah. In addition, this study identifies the uses of insects by ethnics in these two areas. The next objective was to compare the ethnoentomological knowledge in Malaysia with other countries and produce a compilation of ethnoentomological information in Malaysia. The method used in this study were interviews, desktop research and specimen’s collection. The study revealed ten orders of insects used in Peninsular Malaysia and 12 orders in Sabah. For both areas, insects were used as food, medicine, in beliefs and for other purposes such as bait and entertainment. Throughout Malaysia, 12 insects orders used were Hymenoptera; Coleoptera; Orthoptera; Homoptera; Lepidoptera; Hemiptera; Odonata; Blattodea; Mantodea; Phasmatodea; Diptera and Neuroptera while elsewhere, 13 orders were used with the addition of Trichoptera and Plecoptera but excluding Phasmatodea. The analysis of the data found that insects contain minerals, vitamins and proteins. The chemical properties of insects included anti-inflammatory, antibacterial and others. The chemical data acquisition can support the claim of the respondents. Ten species of insects that are commonly used in Malaysia, along with information on taxonomy, ecology, ethnoentomology and chemical contents were compiled as a documentation of ethnoentomology in Malaysia. Insect’s voucher collections were deposited at Universiti Tun Hussein Onn Malaysia. In conclusion, knowledge documentation is very valuable and scientific studies on insects have to be carried out to support the claims made by the respondents.